Performance Evaluation of Fabricated Hybrid Composite Structures for Robot Applications – A Review - Nageswara Rao Manchi, Arockia Selvakumar.A (International Journal of Advanced Science and Technology, 2020)
Robot applications are becoming needy in the present scenario of human life in both developing and developed countries in various applications such as space, automobile, marine industries and home needs, etc. The durability of materials in robotic construction in the present era also a major criterion in shape based robotic development. Even though some researches focus on materials with lightweight like alumina, fiber, etc., there is a lack of economized base high strength composite material. Methods of development in fiber-based composites and its strengthening properties also discussed with application replacements. The objective of this study based on material properties with respect to robot manipulator performance criteria, by which optimum results could be obtained based on experimental and analytical evidence carried out by the past researchers and the need of future work.